2015
DOI: 10.1136/bjsports-2015-094619
|View full text |Cite
|
Sign up to set email alerts
|

Safeguarding the child athlete in sport: a review, a framework and recommendations for the IOC youth athlete development model

Abstract: Participation in sport has many physical, psychological and social benefits for the child athlete. A growing body of evidence indicates, however, that sport participation may have inherent threats for the child’s well-being. The subject of safeguarding children in sport has seen an increase in scientific study in recent years. In particular, there is increasing emphasis on identifying who is involved in abuse, the context of where it occurs and the identification of the various forms of abuse that take place i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 23 publications
5
123
1
Order By: Relevance
“…Reported prevalence rates for the use of any medication during international football, athletics and multisport events range between 35% and 69%; however, these rates relate to physicians’ reports on all athletes 14–17. Several authors18 19 have suggested that excessive medication use is an issue in elite sport and may in fact inhibit recovery after injury 20 21. Future studies should evaluate medication use during aquatic championships in all athletes for comparison with data from other sports.…”
Section: Discussionmentioning
confidence: 99%
“…Reported prevalence rates for the use of any medication during international football, athletics and multisport events range between 35% and 69%; however, these rates relate to physicians’ reports on all athletes 14–17. Several authors18 19 have suggested that excessive medication use is an issue in elite sport and may in fact inhibit recovery after injury 20 21. Future studies should evaluate medication use during aquatic championships in all athletes for comparison with data from other sports.…”
Section: Discussionmentioning
confidence: 99%
“…The only large-scale study available is from the UK, which reported a prevalence of psychological abuse of 75%, raising concerns that this may be the most urgent safeguarding concern in youth sport 38 39. Psychologically abusive behaviours described by athletes generally reflect those described by the WHO and the UN Convention on the Rights of Children 35 38 40 41.…”
Section: Forms Of Abuse and Harassment In Sportmentioning
confidence: 99%
“…Eliminating non-accidental violence against athletes is also part of a broader international conversation in sport addressing ethical and integrity issues, such as doping, match manipulation, event security and fair play 39 174–182. This focus reflects a wider societal discourse regarding abusive and unethical practices in institutional settings, such as the church, healthcare and the military, igniting public interest in the prevention of abuse more broadly, and highlighting the importance of rigorous safe sport business practices 183 184…”
Section: Prevention Of Harassment and Abusementioning
confidence: 99%
“…Sexual abuse has been categorised as a relational threat to child athletes. In the Nassar case, the abuse can also be classified as an organisational threat with the added complexity that the abuse included medical mismanagement4 (see table 1). From the published science in this field, we know that sexual abuse occurs at all levels of sport and in all sports,5 6 and that elite athletes have a higher prevalence 6 7…”
Section: What Is Sexual Abuse In Sport?mentioning
confidence: 99%